2018
DOI: 10.3892/ol.2018.9255
|View full text |Cite
|
Sign up to set email alerts
|

miR‑199b‑5p inhibits triple negative breast cancer cell proliferation, migration and invasion by targeting DDR1

Abstract: Triple negative breast cancer (TNBC) has received increasing attention from oncologists worldwide due to its poor prognosis and paucity of targeted therapies. MicroRNAs (miRs) are a group of small non-coding RNAs that are responsible for the post-transcriptional regulation of various target genes. The present study demonstrated that the expression of miR-199b-5p in breast cancer tissue was significantly reduced compared with that in normal breast tissues by reverse transcription-quantitative polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…In triple negative breast cancer (TNBC) cells, miR-199b suppresses cell proliferation and invasion by directly targeting DDR1. 38 BC patients who showed lower expression level of miR-199b had poorer overall survival rate than those with high level. Furthermore, it is indicated that low expression of miR-199b is correlated with poor prognosis, advanced TNM stage, and positive lymph node metastasis in BC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In triple negative breast cancer (TNBC) cells, miR-199b suppresses cell proliferation and invasion by directly targeting DDR1. 38 BC patients who showed lower expression level of miR-199b had poorer overall survival rate than those with high level. Furthermore, it is indicated that low expression of miR-199b is correlated with poor prognosis, advanced TNM stage, and positive lymph node metastasis in BC.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that miR‐199b acts as a tumor suppressor in BC. In triple negative breast cancer (TNBC) cells, miR‐199b suppresses cell proliferation and invasion by directly targeting DDR1 . BC patients who showed lower expression level of miR‐199b had poorer overall survival rate than those with high level.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies documented that DDR1 expression can be regulated at the transcription level by factors such as tumor protein p53 (TP53) and zinc finger E-box binding homeobox 1 (13) or promoter CpG methylation (49). DDR1 expression may be also controlled post-transcriptionally by the two highly similar miRs, miR-199a-5p and miR-199b-5p as found in hepatocellular carcinoma (35), acute myeloid leukemia (42), colorectal cancer (37), cutaneous squamous cell carcinoma (39) or triple-negative breast cancer (54). The expression levels of miR-199a-5p or miR-199b-5p were negatively correlated with DDR1 protein content in the ccRCC tissues, suggesting that those two miRs may repress DDR1 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%